Sweetpotato bread for better nutrition-South Africa. Tackling malnutrition and driving business growth. Project profile. - International Potato Center (International Potato Center, 2020)
This project investigates the potential for introducing sweetpotato-enriched bread to South Africa. Beyond the benefits for family nutrition, it seeks to support farmers by increasing demand for valueadded sweetpotato products.